Teachers Experiences on Blended Learning: a Case Study of a Group of Secondary School Teachers in Malaysia and Indonesia - Hayati, Susruhiyatun; Armansah, Youdi; Ismail, Siti Farah Adilah Binti (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study is to identify the experiences and challenges of teachers in using the blended learning method during the teaching and learning process. This study used a case study method with a qualitative approach. This case study was conducted through interview with 6 of respondents involves the group of secondary school teachers from Malaysia and Indonesia. The instrument used is open-ended questions. The collected data were analyzed using descriptive. The results showed that the blended learning environment was built with a combination of face-to-face and online sessions. This case study found common challenges that was faced by teachers are the students’ lack of devices and equipment. From the results, teachers explained how dissatisfied they were in order to deliver information towards their students. Teachers' experiences of engaging the students in a blended learning class by getting attention and students interest with fully applying technology. Practice with technology-mediated learning creates challenges that must be taken into account when planning and implementing integrated teaching and learning. The challenges that the teachers face in engaging the students in a blended learning class from 3 factors: First factor from environmental factors is lack of internet connection so that it hinders the blended learning process, second factors that come from students are lack of students' interest and student motivation, take a lot more time, students lazy during online class, students pay less attention and maintain consistency of participants in the class, and the last factor that comes from the teacher is unable to be assessed students task. However, it provides a good opportunity to enhance student learning using blended learning methods.